The practice of womens social capital as the pillars of the family economic in rural area - Rahel Widiawati Kimbal (Association for Scientific Computing Electrical and Engineering (ASCEE), 2021)
This study aims to find various forms of women’s social practices as the pillars of the family economic in rural UIK. The research employs qualitative research method which involves a study case at Kacang Tore Small Enterprise. The data of the research were collected by using triangulation method covering observation, interview, and documentation, and those data obtained in this research were then analyzed using a forward stepwise model from Spradley. From the findings, it is stated that social capital is formed by the presence of several elements of social capital which created through social interactions between economic actors, and women workers. Its form can be seen through various forms of social capital such as beliefs, networks, norms, values of life based on religious teachings and ancestral cultural heritage which passed down over generations to generations by exchanging kindness. The practice of women’s social capital, the pillars of the family economy, is found in terms of (1) building trust in a working relationship in all activities of the small business unit; (2) establishing social capital network which emerges from relationships between family members and friends; (3) maintaining kindness and reciprocity embedded in free knowledge sharing and giving loan; (4) preserving the values of life as having been explained in religious teachings and in cultural heritage passed down from the generation to generation; (5) implementing norms as the guideline for all economic actors to conduct their economic activities. These practices are essential to strengthen the existence of small business unit at the rural area, which then provide the recommendation for other small business units throughout Indonesia to empower women as the pillar of the family. Empowering women is believed to increase the family economy because women serve as the ideal capital resources for maintaining the economic resilience of the family.